RELATIONSHIP BETWEEN EMPOWERMENT AND MOTIVATION WITH TEACHER COMMITMENT - Masduki Ahmad (Akademika : Jurnal Teknologi Pendidikan, 2021)
This study aims to determine whether or not there is a correlation between empowerment and motivation with teacher commitment at SDN Duren Sawit, East Jakarta. This study decides the three variables used, namely empowerment (X1), motivation (X2), and teacher commitment (Y). This study uses quantitative research using a survey method using a correlational approach. The subjects of this study were teachers from 8 public elementary schools located in the Duren Palm Village, East Jakarta, with a total population of 140 teachers. Sampling was carried out using Simple Random Sampling with the formula Slovin at a significance level of an error level of 5% so that it obtained 104 sample members. Carried out this research from January 2021 to July 2021. Testing the hypothesis was carried out using a multiple linear Unified regression model using a coefficient of determination (R Square) of 0.664 or 66.4%. From the results that have been carried out when testing the hypothesis, it is known that the results of this study have a relationship between empowerment and motivation with teacher commitment at SD Negeri Duren Sawit, East Jakarta.